Pengaruh Variabel Eksternal Dan Internal Terhadap Harga Saham Sub Sektor Properti Indeks LQ45 Periode 2018-2020 - Alfin, Muhamad; Bachtiar, Arief (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The research objective is to find out whether inflation, exchange rates, GDP, interest rates, Net Indonesian Exports, and the Dow Jones Index have an influence on the stock price of the property sub-sector in LQ 45. This research uses a quantitative approach. The sample population of this study consists of business actors engaged in the property sector sector who are scheduled to follow the LQ45 index during the coverage period, namely 2018-2020 with a total of 154 samples. The results showed that 1) Inflation has a positive and significant effect on the share price of the property sector in the LQ45 Index. 2) Interest rates have a negative and significant effect on the stock price of the property sector in the LQ45 Index. 3) GDP has a positive and significant effect on the stock price of the property sector in the LQ45 Index. 4) The exchange rate has a negative and significant effect on the share price of the property sector in the LQ45 Index. 5) Net exports have no influence on the share price of the property sector in the LQ45 Index. 6) DJI has a significant positive effect on the stock price of the property sector in the LQ45 Index.